ANALISIS KRITIS METODE CERAMAH DALAM PEMBELAJARAN AKIDAH AKHLAK DAN OPTIMALISASI STRATEGI PEDAGOGIS UNTUK PENINGKATAN KERELIGIUSITAS SISWA SEKOLAH DASAR (STUDI KASUS KONTEKSTUAL SDN 16 KOTA BENGKULU) - Fira Fauzia; Tri Utami Ramadani; Gekia Afiani; Yunda Mardatillah; Arini Julia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the lecture method in Islamic Religious Education (PAI) and to formulate alternative learning strategies that are more relevant to the needs of contemporary students. Although the lecture method has long been considered practical and easy to apply, recent findings indicate that it is no longer adequate in promoting active participation, deep understanding, and character development among learners. This research employs a qualitative approach through library research supported by empirical observations in several schools in Bengkulu. The results show that the lecture method positions students as passive listeners, leading to low engagement, reduced motivation, and limited learning outcomes. Through comparative analysis of active learning strategies such as the Value Clarification Technique (VCT), storytelling, and role playing, this study proposes more effective alternatives suited to modern learners' characteristics. These methods have been shown to enhance classroom interaction, strengthen conceptual understanding, and cultivate moral values through meaningful learning experiences. The study recommends integrating active learning approaches as primary strategies in PAI instruction while considering students’ needs and the contextual conditions of each school.